Risk of underdiagnosis of hypertension in schizophrenia patients - Miguel Castillo-Sánchez; Mireia Fàbregas-Escurriola; Daniel Bergè-Baquero; MªIsabel Fernández-San Martín; Quintí Foguet Boreu; Albert Goday-Arno (Clinical and Experimental Hypertension, 2018)
Aim: Arterial hypertension requires proper screening and management, and its underdiagnosis in patients with schizophrenia (SZ) and/or antipsychotic treatment has been postulated. The objective of the study is to assess whether there are differences in the proportion of screened patients with a blood pressure >140/90 mmHg that are undiagnosed or not confirmed later (risk of underdiagnosis). Methods: Cross-sectional study of clinical records from SIDIAPQ (Spain) during the 2006–2011 period. Three groups were studied: SZ, no SZ but under antipsychotic treatment, and control groups. Patients with established hypertension, cardiovascular disease, dementia, or diagnosis of SZ or starting with antipsychotic treatment during this period were excluded. Results: The SZ group had a lower risk of underdiagnosis than the control group (OR 0.91; 95% CI: 0.83–0.99; p < 0.05), at the expense of men (OR 0.8; 95% CI: 0.71–0.9; p < 0.001) and patients younger than 50 years of age (OR: 0.84; 95% CI: 0.74–0.93; p < 0.003). In the no SZ but under antipsychotic treatment group there were some differences, but not in the overall results. Conclusion: Preventive management of hypertension seemed to be sufficient for SZ and antipsychotic treatment patients. The lower prevalence of hypertension found in these groups may be due to other factors (blood pressure-lowering effect of psychoactive drugs or smoking) but these hypotheses must be evaluated with specific studies.